Covid 19 enfeksiyonu geçiren sağlık çalışanlarının depresyon anksiyete ve stres düzeylerinin belirlenmesi - Demir, Zeynep (My University, 2022)
Amaç: COVID 19 enfeksiyonu geçiren sağlık çalışanlarının depresyon, anksiyete ve stres düzeylerini belirlemektir Yöntem: Haziran – Ağustos 2021 tarihleri arasında yapılan bu çalışma bir vaka kontrol çalışmasıdır. Çalışmanın örneklemini, İstanbul’da bir şehir hastanesinde çalışan, COVID 19 enfeksiyonu geçiren (vaka grubu n: 371) ve COVID 19 enfeksiyonu geçirmemiş olan (kontrol grubu n:112) 483 sağlık çalışanı oluşturmuştur. Veri toplama araçları Kişisel Bilgi Formu ve Depresyon Anksiyete Stres Ölçeğidir. Etik kurul izni, katılımcı onamı ve ölçeği geliştiren Akın’ dan izin alınmıştır. Bulgular: Vaka grubunun %61,5’ i kadın %38,5’ i erkek, kontrol grubunun ise %57,1’i kadın %42,9 erkek. Vaka grubunun %17,3’ ü doktor, %53,’i hemşire %29,4’ ü diğer sağlık çalışanıdır. Kontrol grubunun ise %8,8’i doktor, %67’si hemşire %24,2’ si diğer sağlık çalışanıdır. Katılımcıların meslekleri ile Depresyon Anksiyete Stres Ölçeği puanları arasında istatistiksel olarak anlamlı bir farklılık görüldü (p<0.05).Vaka grubunun depresyon puan ort. 13,62 ± 8,83(hafif), anksiyete 14,01±8,09(orta), stres 15,25± 8,76 (hafif)’dir. Kontrol grubunun depresyon puan ort. 12,79±5,26(hafif), anksiyete 14,34±4,81, (orta) ve stres 15,06±5,5,(hafif)’dir. Puan ortalamaları arasında istatistiksel olarak anlamlı bir fark yoktur (p>0,05). Sonuç: Sonuç olarak, pandemi, COVID 19 enfeksiyon geçirsin veya geçirmesin tüm sağlık çalışanlarında depresyon, anksiyete ve strese benzer düzeyde neden oluşturmuştur.

Purpose: To determine the depression, anxiety and stress levels of healthcare workers with COVID 19 infection. Method: This study, conducted between June and August 2021, is a case-control study. The sample of the study consisted of 483 healthcare workers working in a city hospital in Istanbul, who had COVID 19 infection (case group n: 371) and who did not have COVID 19 infection (control group n: 112). Data collection tools are Personal Information Form and Depression Anxiety Stress Scale. Ethics committee permission, participant consent, and permission from Akın, who developed the scale, were obtained. Results: 61.5% of the case group was female, 38.5% was male, and 57.1% of the control group was female and 42.9% male. 17.3% of the case group are doctors, 53% are nurses, 29.4% are other health workers. In the control group, 8.8% are doctors, 67% are nurses, and 24.2% are other health workers. There was a statistically significant difference between the occupations of the participants and the Depression Anxiety Stress Scale scores (p<0.05). The mean depression score of the case group. 13.62 ± 8.83 (mild), anxiety 14.01±8.09 (moderate), stress 15.25± 8.76 (mild). Depression score mean of the control group. 12.79±5.26(mild), anxiety 14.34±4.81 (moderate), and stress 15.06±5.5(mild). There was no statistically significant difference between the mean scores (p>0.05). Conclusion: As a result, the pandemic caused a similar level of depression, anxiety and stress in all healthcare workers, whether they had COVID 19 infection or not.
Keywords: anksiyete; anxiety; COVID 19; COVID-19 (Disease); COVID-19 (Hastalık); depression; depresyon; Psikolojik yönleri; Psychological aspects; stres; stress